2018
DOI: 10.2174/1874312901812010129
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mean Platelet Volume in Patients with Systemic Lupus Erythematosus

Abstract: Introduction:The Mean Platelet Volume (MPV) is a platelet activation biomarker that has been recently correlated with disease activity in SLE. We aimed to evaluate the MPV in patients with SLE comparing it with healthy individuals, to study the correlation between MPV and SLE Disease Activity Index (SLEDAI) in SLE patients and to analyze possible correlation between MPV and Erythrocyte Sedimentation Rate (ESR), C-Reactive Protein (CRP), and complement components C3 and C4.Methods:This is a cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 35 publications
1
19
0
1
Order By: Relevance
“…The rapid, sensitive, and specific evaluation of disease activity in patients with SLE are important for short-term and longterm treatment planning. Previous studies have shown that inflammatory factors, including tumor-necrosis factor-a (TNF-a), complement C3, complement C4, the mean platelet volume, the neutrophil to lymphocyte ratio, IL-6, and IF-34, were associated with the severity of SLE [3,[16][17][18][19]. The findings from these previous studies support that inflammatory cytokines play an essential role in the pathogenesis and etiology of SLE.…”
Section: Discussionmentioning
confidence: 73%
“…The rapid, sensitive, and specific evaluation of disease activity in patients with SLE are important for short-term and longterm treatment planning. Previous studies have shown that inflammatory factors, including tumor-necrosis factor-a (TNF-a), complement C3, complement C4, the mean platelet volume, the neutrophil to lymphocyte ratio, IL-6, and IF-34, were associated with the severity of SLE [3,[16][17][18][19]. The findings from these previous studies support that inflammatory cytokines play an essential role in the pathogenesis and etiology of SLE.…”
Section: Discussionmentioning
confidence: 73%
“…Hartmann et al. 12 found that no correlation between MPV and CRP, ESR, C3 and C4.Also, Delgado-García et al. found no correlation between MPV and ESR (p = 0.26).…”
Section: Discussionmentioning
confidence: 96%
“…Also, Hartmann et al. 12 and Delgado-García et al. 13 found that adult patients with active SLE had decreased MPV when compared to inactive disease group.…”
Section: Discussionmentioning
confidence: 98%
“…Data on the usefulness of the MPV in other inflammatory diseases are divergent. In the acute phase of rheumatic diseases, a decrease in MPV [33,34] or its increase associated with higher activity of juvenile idiopathic arthritis, psoriatic arthritis, SLE may occur [5,35,36]. Some studies indicate the usefulness of MPV in monitoring anti-inflammatory therapy in rheumatoid arthritis [37].…”
Section: Discussionmentioning
confidence: 99%